2020
DOI: 10.1088/1361-6463/abbb49
|View full text |Cite
|
Sign up to set email alerts
|

All-MBE grown InAs/GaAs quantum dot lasers with thin Ge buffer layer on Si substrates

Abstract: A high-performance III-V quantum-dot (QD) laser monolithically grown on Si is one of the most promising candidates for commercially viable Si-based lasers. Great efforts have been made to overcome the challenges due to the heteroepitaxial growth, including threading dislocations (TDs) and anti-phase boundaries (APBs), by growing a more than 2 µm thick III-V buffer layer. However, this relatively thick III-V buffer layer causes the formation of thermal cracks in III-V epi-layers, and hence a low yield of Si-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 46 publications
0
20
0
2
Order By: Relevance
“…In addition, the thermal energy distribution of electrons in the quantised DoS is significantly decreased, which makes the QD temperature-insensitive compared with other higher dimensional structures [31]. This is experimentally proved by the maximum operating temperatures of QD lasers on GaAs native and Si substrates as high as 220 °C [55] and 130 °C [56], respectively, which are well beyond the requirement in datacom and telecom applications; for instance, a typical operating condition in data centres is ~80 °C. Reproduced with permission from Ref.…”
Section: Advantages Of Qdsmentioning
confidence: 99%
“…In addition, the thermal energy distribution of electrons in the quantised DoS is significantly decreased, which makes the QD temperature-insensitive compared with other higher dimensional structures [31]. This is experimentally proved by the maximum operating temperatures of QD lasers on GaAs native and Si substrates as high as 220 °C [55] and 130 °C [56], respectively, which are well beyond the requirement in datacom and telecom applications; for instance, a typical operating condition in data centres is ~80 °C. Reproduced with permission from Ref.…”
Section: Advantages Of Qdsmentioning
confidence: 99%
“…This can be explained by that the defects of which the form is less diverse and more mobile may annihilate during growth and coalescing. In addition, a three-step growth, the modified two-step growth method in which an intermediate-temperature (IT) layer is added between LT and HT layer, was commonly employed in recent years [128,[141][142][143]. Nozaki et al [144] proposed and reported that the three-step growth method in GaAs-on-Si improved the surface morphology, as well as crystallinity.…”
Section: Nucleation and Iii-v Buffer Layermentioning
confidence: 99%
“…Because the cracks were preferentially formed at the edges of the notches acting as stress concentrators, the periodic crack arrays could be achieved, resulting in a crack-free region (2 × 2 mm 2 ) where 5.8 µm-thick GaAs-based solar cell structures were grown. Recently, instead of a thick GaAs buffer layer, growing a thin Ge layer on Si was proposed [143,247]. For example, Yang et al [143] demonstrated that although a 300 nm-thick thin Ge layer replaced the conventional 1 µm-thick GaAs buffer layer for InAs/GaAs QD lasers on Si, the fabricated lasers with thin Ge buffer showed comparable performances, in terms of TDD and lasing behavior, to the conventional QD lasers with thick GaAs buffer.…”
Section: Minimizing Thermal Cracksmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, quantum dot (QD) is a three-dimensional restricted quasi-zerodimensional material with a density of states of the delta function, called "artificial atoms", which exhibits brilliant material advantages, high characteristic temperature, high modulation bandwidth, high differential gain, low threshold current density, insensitivity of threshold current density to IOP Publishing doi:10.1088/1742-6596/2226/1/012006 2 temperature and no chirp working under direct modulation, etc. [7][8][9][10][11][12][13][14] It is worth pointing out that quantum dots are widely applied as the active area materials in the Ⅲ/Ⅴ integrated technology owing to their insensitivity to defects [15,16] .…”
Section: Introductionmentioning
confidence: 99%